Keragaan Agribisnis Usaha Jamur Tiram Putih di Kelurahan Anduonohu Kecamatan Poasia Kota Kendari (Studi Kasus di Usaha Tiga Putra Farm) - Rahmat Agus Santoso; La Ode Alwi; Abdul Gafaruddin (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
Oyster mushroom is a type of wood mushroom that Indonesia commonly consumes. It has a fruiting body that grows in bloom to form a shallow funnel shell (oyster). This study aimed to determine the agribusiness performance of the White Oyster Mushroom (Pleurotus ostreatus) in Anduonohu ​​Village, Poasia District, Kendari City. Case study on Tiga Putra Farm Business. This research was conducted in September 2021. The object of this research was the Tiga Putra Fram Timber Mushroom business. The method used in this study is Qualitative Descriptive Analysis. The type of data in this study used primary data, namely direct interviews, and secondary data, namely library literature. The variables used in this study are 1. The informant's identity includes age, education level, business experience, and some family dependents, 2. Agribusiness performance from this study is in the form of support in the agribusiness subsystem, which includes production facilities (seeds, fertilizers, tools /machinery, and mushroom house), cultivation and farming subsystem (planting, maintenance, processing), and marketing subsystem (distribution). The results of this study are the agribusiness performance of the white oyster mushroom (Pleurotus ostreatus), namely the procurement and provision of production facilities, including the procurement of mushroom houses, seeds, tools, and machines. Cultivation and farming include oyster mushroom production, maintenance, and harvest. Oyster mushroom product marketing is done online and offline by online method, namely posting oyster mushroom products on several social media platforms such as Facebook, WhatsApp, and Instagram. Thus the range of product marketing can be more comprehensive. Offline marketing to resellers of oyster mushrooms that will be resold, such as the Ummushabri Kendari and Hypermart.